2010
DOI: 10.1302/0301-620x.92b1.22241
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe extra-articular contracture of the elbow by open arthrolysis and a monolateral hinged external fixator

Abstract: Arthrolysis and dynamic splinting have been used in the treatment of elbow contractures, but there is no standardised protocol for treatment of severe contractures with an arc of flexion < 30 degrees . We present our results of radical arthrolysis with twin incisions with the use of a monolateral hinged fixator to treat very severe extra-articular contracture of the elbow. This retrospective study included 26 patients (15 males and 11 females) with a mean age of 30 years (12 to 60). The mean duration of stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…We achieved a better gain in amplitude when compared with the group of Tosum et al [7] but worse than Kulkarni et al [23] and Liu et al [5] who had superior results in AOM gain. The difference in our results and two latter series could be caused by more restricted preoperative motion in those two groups.…”
Section: Discussionmentioning
confidence: 44%
“…We achieved a better gain in amplitude when compared with the group of Tosum et al [7] but worse than Kulkarni et al [23] and Liu et al [5] who had superior results in AOM gain. The difference in our results and two latter series could be caused by more restricted preoperative motion in those two groups.…”
Section: Discussionmentioning
confidence: 44%
“…These findings are encouraging compared with the results of other studies that reported improvement of 87° and 89°. 25,26 Furthermore, these authors 25,26 applied a hinged external fixator to assist postoperative rehabilitation (as was done in the current study), and results were much better than those achieved with open release alone. 20 The use of a hinged external fixator in this way differs from its typical use as a salvage to restore joint stability and optimize rehabilitation.…”
Section: A E481mentioning
confidence: 65%
“…However, subsequent to numerous reports of successful procedures , arthrolysis is now regarded as a reliable, rewarding, evidence-based operation, with low risk of complications. The results in the recent literature are broadly similar, reporting that elbow motion improves in almost all patients, with a mean gain of approximately 50 • , and that the majority achieve the functional arc of 30 • to 130 • [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The key principles common to almost all studies are the achievement of as much movement as possible at surgery and early motion postoperatively, which requires adequate pain control ( Fig.…”
Section: Surgicalmentioning
confidence: 65%